Penerapan Bimbingan Kelompok untuk Meningkatkan Kemampuan Beradaptasi Siswa Sekolah Menengah Kejuruan - Lusikooy, Andretha Mariana (Guidance and Counseling Study Program, Pattimura University, 2017)
This research is a Classroom Action Research which aims to obtain data through cycles in treatment that is done through group guidance approach to adaptation of students. This study was conducted in two cycles with a duration of research for three months. The final result is: From 38 students as the subject is known 36 students or 95% of students are able to solve their problems with the form of adjustment in the classroom, school and community. 2 students or 5% of students still need individual guidance. Thus it is stated that the research using this group guidance method is very effective in solving student persolan through adaptation (adaptation) with the community both in the scope of SMK Negeri 2 Ambon or among student residence.